Persepsi Masyarakat Banyumas Tentang Program Studi Studi Agama-Agama - Ma'ruf, Muamar (AL-ADYAN, 2020)
The purpose of the paper is to examine various perceptions of the Banyumas community about the Study Program of Religions, because there are many assumptions that aren't in accordance with the reality of the study program. Socio-Cultural theory is used in obtaining data that will be presented, because in addition to carriying out a social approach, researcher also try to find out the culture that exists in certain local communities with in the scope of Banyumas Regency. The data obtained is the result of observation, namely plunging directly into the field by conducting interviews with the Banyumas community regarding their views on what is the Study of Religions by only knowing literally. Therefore from this observation, there are number of points generated namely; First, get data related to the views of the general public in Banyumas itself. As for the data in the form of good and bad comments related to the Study of Religions and various views that arise from an understanding that is limited to knowing about what is the Study of Religions literally. Second, can convey information to the public about the actual facts of the Study of Religions. At this point, the researcher focused more on the process of oral dilivery dilivered to the Banyumas community itself. While the method used in this resarch is through a social approach to the community (social experiment).